Empirical Analysis of Factors Preventing Pupils from Choosing stem Fields - Šarpanov, Roman (Jaunųjų mokslininkų darbai, 2024)
As technological developments expand globally, the need for science, technology, engineering, and math (STEAM)-relate d professions has grown. Emphasis on STEAM-oriented careers and study choices has expanded in many educational systems in the world. The research focuses on students‘ attitudes towards STEM subjects inside and outside of school, their motivation to study and pursue a STEM career. Key results indicate that students have reservations in pursuing a STEAM career and that their academic and practical motivation to study STEAM varies. The study suggests that employing a diverse, practical approach towards teaching STEAM subjects could encourage more students to choose STEAM subjects and careers. Research object is to explore the factors associated with the low number of students choosing to study and pursue careers in STEM (Science, Technology, Engineering, Mathematics) fields after secondary education in Lithuania. Aim of research is to understand the factors influencing the choices of young people in Lithuania regarding STEM subjects and careers. Objectives: 1. To identify and analyse the factors that prevent students from choosing STEM fields; 2. To explore the differences in attitudes and motivations towards STEM between male and female students. Method of research: Conducting a quantitative analysis through online surveys involving 196 high school students from Šiauliai, Lithuania.